THE EFFECT OF CLEAN LIVING BEHAVIOR ON THE IMPROVEMENT OF STUDENTS’ACHIEVEMENT - Ranta Butarbutar (Universitas Musamus, 2019)
Clean living behavior has effect on the student’s learning achievement. This study aims to determine the effect of clean living behavior on the improvement of students’ learning achievement in Tomer Elementary School Naukenjerai District on Academic Year of 2017/2018. The type of this research is a correlational research. The method used is survey research, with data collection technique using questionnaire and documentation analysis. The population of this study is the students of class I to class VI, which consists of 50 students, taken using random sampling technique. The findings of this study indicate that there is a significant effect between clean living behavior on the improvement of students’ learning achievement in Tomer Elementary School Naukenjerai District on Academic Year of 2017/2018. From the total of 50 students, there are only 5 students (10%) who have clean living behavior (low category), while the rest of 45 students (90%) have not implemented a clean living behavior (high category). Keywords: clean living behavior; improvement; learning achievement